2009
DOI: 10.1016/j.ijid.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia due to Clostridium difficile—review of the literature

Abstract: Extracolonic Clostridium difficile infections have been infrequently reported. Extracolonic manifestations of C. difficile include bacteremia, intra-abdominal abscess, osteomyelitis, visceral abscess, empyema, reactive arthritis, and small bowel disease with formation of pseudomembranes on ileal mucosa. Most cases of extracolonic C. difficile have been preceded by gastrointestinal disease, either C. difficile colitis or surgical and anatomical disruption of the colon. Bacteremia due to C. difficile has previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 22 publications
4
88
0
1
Order By: Relevance
“…13 Clearly established risk factors include: age above 65 years, co-morbidities, immune-suppression, cancer, gastrointestinal disorders, previous antibiotic use, and previous hospitalization.…”
mentioning
confidence: 99%
“…13 Clearly established risk factors include: age above 65 years, co-morbidities, immune-suppression, cancer, gastrointestinal disorders, previous antibiotic use, and previous hospitalization.…”
mentioning
confidence: 99%
“…C. difficile toxins might, therefore, cause mucosal damage resulting in bacteremia. 3) A review by Libby et al 6) found that all adult patients with C. difficile bacteremia had concomitant gastrointestinal pathology such as diarrhea, small bowel obstruction, or ischemic colitis, which may compromise the integrity of the gastrointestinal tract. They reported that C. difficile bacteremia was strongly associated with prior antibiotic exposure but that there was no significant association between C. difficile arteritis and colonic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, the atherosclerotic lesions in the occluded arteries, where oxygen delivery and pH were reduced, provided an environment where C. difficile was able to grow and form a mycotic aneurysm. Libby et al 6) reported that compromised immunological status was associated with extracolonic C. difficile infection. In our patient, chronic renal failure may have contributed to providing suitable conditions for C. difficile to infect the atherosclerotic lesions.…”
Section: Case Reportmentioning
confidence: 99%
“…Intravenous vancomycin and metronidazole were commonly used (Lee et al, 2010;Libby & Bearman, 2009). A crude mortality rate of up to 50 % was reported by Libby & Bearman (2009) for C. difficile bacteraemia. It is, however, difficult to attribute this solely to the bacteraemia as most of the cases had severe underlying pathology that could have been the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases are usually preceded by gastrointestinal infection. Often, mixed infections with other gut pathogens are found (Libby & Bearman, 2009;Spencer et al, 1984). However, it is difficult to interpret the clinical relevance of such isolates from extra-intestinal sources and in some cases they may only represent contamination with faecal commensals.…”
Section: Introductionmentioning
confidence: 99%